Tourism Marketing as a Community Service Tool: A Case Study of Iraqi Airways Offices - Ahmed Taha Hameed; Ahmed Akram Ali; Hawara Abbas Fadel (Peerian Journals Publishing, 2025)
Tourism marketing is one of the most important tools for achieving sustainable development, as well as for developing the local economy and maximizing resources. It also works to attract tourists and promote the country's tourist attractions. Iraq possesses numerous tourist attractions, whether natural, archaeological, historical, heritage, cultural, or religious. Therefore, the role of tourism organizations is no longer limited to increasing resources but extends to serving the community and fulfilling social responsibility.
Keywords: Tourism marketing; Iraqi Airways; community service